Religiusitas Dan Stres Menghadapi Ujian Nasional Pada Siswa Sma Kelas XII - Kirana, Adeline Vania; Rustam, Amrizal (Happiness: Journal of Psychology and Islamic Science, 2019)
Ujian Nasional is one of the biggest stressor for the 12th grade high school students. Previous studies found that high school students who took the Ujian Nasional experience stress. It’s known that exam stress could cause a failure in exam. Religiosity is known to have negative relationship to one’s stress state. The purpose of this study is to test the relationship between religiosity and exam stress on 12th grade high school students who will have to take the Ujian Nasional. The hypothesis of this study is there’s a negative relationship between religiosity and exam stress. The Product Moment correlation technique by Pearson is used to examine the relationship between two variables. Result of this research is that there’s a significant negative relationship between religiosity and student’s exam stress (p < 0,01, r = 0,212). Exam stress on students could be reduced by increasing their religiosity.